Intentional harm, accessories and conspiracies - Davies, P; Sales, P (Sweet and Maxwell, 2018)
Assesses the principles about conspiracy tort which can be derived from OBG Ltd v Allan (HL), Customs and Excise Commissioners v Total Network SL (HL) and Fish & Fish Ltd v Sea Shepherd UK (SC), including how they clarify its relationship with the tort of intentional infliction of harm by unlawful means and the concept of accessory liability. Suggests why criminal law and economic torts are unhelpful for determining civil liability for conspiracy.